Study of the structure of a pollution of water bodies through the Itô process - Osadchiy, V. I.; Kovalchuk, L.A.; Osadcha, N.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
The significant separation of the observed concentrations of chemical components of surface waters into the natural and anthropogenic components by testing two hypotheses for Itˆo processes is implemented. It is experimentally confirmed that the basis of changes in the concentrations of ingredients is the Wiener process, which opens the way to research the directedness of hydrochemical processes, by using the statistics of random processes.